The Power of Sex Localization Closure in Dolly Surabaya - Lusi Andriyani; Chusnul Mar’iyah (Universitas Al Azhar Indonesia, 2019)
Abstract - Dolly is part of the Surabaya city which is located in Putat Jaya District. The money flows in Dolly for a night reached 1 billion rupiah. This fact forced people from some groups to take benefits in Dolly’s economy activities. In other hand, social groups were still strongly maintain the moral aspects from Dolly closure, escpecially for children rights protection. Children about 14 to 16 years old often became the actors from human trafficking that offered their own friends. Beside that, children at lower ages acted as sex addict from sex media. These findings informed us the Dolly closure were not easy. As Risma, the Surabaya Mayor, Dolly closure was a must that would need a strong effort to manage and control its impacts. The Dolly closing which conducted on 18 June 2014 had economic, social, and politic impacts. The closing program need to be discuss by all aspects in Surabaya. It should be emphasize people from Dolly to have enough skill for their family income.Keywords – Commercial Sex Worker, Dolly, Power interplay